Strategic Human Resource Management As a Translation System In Digital Transformation: Evidence From Haier Smart Home - Yin LingHu (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Digital transformation often fails at execution because technologies do not automatically alter decision rights, talent allocation, incentives, or cross-boundary coordination. This study examines how strategic human resource management translates digital strategy into organisational action and value creation. A longitudinal embedded single-case study of Haier Smart Home was conducted using six semi-structured interviews (628 recorded minutes) collected in February-March 2026 and archival evidence covering 2020-2025. Gioia coding, process tracing, pattern matching, rival-explanation analysis, and data triangulation were applied. The findings identify four linked mechanisms: dynamic strategic alignment through decentralised authority and human-resource platforms; order-based human-capital reconfiguration through capability labels, opportunity orders, and flexible team boundaries; market-oriented incentives through user-paid compensation and traceable contributions; and platform governance through chain-group collaboration across internal units and ecosystem partners. These mechanisms improve organisational responsiveness and broaden value creation, but their effects depend on reliable data, divisible tasks, attributable feedback, talent depth, transparent rules, and sustained leadership commitment. The study reconceptualises digital human-resource management as a governance mechanism system rather than a set of automated functions.